2006
DOI: 10.1111/j.1365-3040.2006.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing environmental and physiological controls over water relations in a Scots pine (Pinus sylvestris L.) stand through analyses of stable isotope composition of water and organic matter

Abstract: 13C was assumed to be concertedly influenced by Gs and photosynthetically active radiation (PAR) (as a proxy for photosynthetic capacity). We conclude that isotope signatures can be used as effective tools (1) to characterize the seasonal dynamics in source and xylem water, and (2) to assess environmental effects on transpiration and Gs of Scots pine, thus helping to understand and predict potential impacts of climate change on trees and forest ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 75 publications
(144 reference statements)
4
96
2
Order By: Relevance
“…However, these variations in the fast-turnover organic matter pool in leaves had a much lower day-night amplitude than the observed diel changes in respired δ 13 CO 2 (Brandes et al, 2006(Brandes et al, , 2007Gessler et al, 2007Gessler et al, , 2008Kodama et al, 2008;Werner et al, 2009, see Table 1) and were also phase-shifted compared to δ 13 C res (Kodama et al, 2008, see also Fig. 1).…”
Section: M12mentioning
confidence: 96%
See 1 more Smart Citation
“…However, these variations in the fast-turnover organic matter pool in leaves had a much lower day-night amplitude than the observed diel changes in respired δ 13 CO 2 (Brandes et al, 2006(Brandes et al, , 2007Gessler et al, 2007Gessler et al, , 2008Kodama et al, 2008;Werner et al, 2009, see Table 1) and were also phase-shifted compared to δ 13 C res (Kodama et al, 2008, see also Fig. 1).…”
Section: M12mentioning
confidence: 96%
“…2; M1.3). Consequently, the diel cycle of δ 13 C in organic matter in trunks and stems of trees is mainly dependent on the position along the trunk and dampening as well as time lags have been observed (Keitel et al, 2003;Brandes et al, 2006Brandes et al, , 2007. At the tree trunk base often no diel variation in phloem sugar δ 13 C was present Kodama et al, 2008;Betson et al, 2007;Rascher et al, 2010) whereas strong diel variations in δ 13 C res are generally observed (Kodama et al, 2008;Maunoury et al, 2007).…”
Section: M13: Isotope Fractionation During Carbon Transportmentioning
confidence: 97%
“…On the basis of day-to-day variations in the photosynthetic carbon isotope fractionation as occurring in C 3 plants, the transport of new assimilates through the plant and within the ecosystem has been tracked as soil respired CO 2 Knohl et al, 2005;Mortazavi et al, 2005;Brandes et al, 2006;Gessler et al, 2007) and transport times have been assessed (Mencuccini and Hölttä, 2010) (see 3.4). As demonstrated by Brandes et al (2007) and Wingate et al (2010), such techniques can be applied throughout the whole growing season and have the additional advantagecompared to 13 C pulse labeling experiments -that the information on leaf physiology encoded in δ 13 C can be additionally analysed. As mentioned above and discussed by Warren and Adams (2006), it might, however, not be possible to directly relate δ 13 C to p i /p a or water-use efficiency in C 3 species due to potential variations in g m .…”
Section: Photosynthetic Carbon Isotope Fractionation and Its Temporalmentioning
confidence: 99%
“…However, temporal changes in C allocation and metabolic processes along the transport pathways can strongly affect this relationship between environmental conditions and δ 13 C. For example, it has been observed that phloem sucrose is 13 C-enriched in the trunk compared to the twig phloem of trees (e.g. Brandes et al, 2006Brandes et al, , 2007. It is likely that metabolic processes associated with phloem transport (such as phloem loading, unloading and mixing; 5 in Fig.…”
Section: Carbon Allocation In the Plant-soil Systemmentioning
confidence: 99%
“…Some of these biophysical processes may include: effects of evaporative fractionation on xylem isotopic compositions during summer months (Simonin et al, 2014), the potentially longer residence and transit times of water within the xylem (Brandes et al, 2007), or possible 15 fractionation/discrimination of 18 and 2 during root-water uptake (Ellsworth and Williams, 2007;Vargas et al, 2017).…”
Section: Ecohydrologic Controls Of Root-uptake On Soil Watermentioning
confidence: 99%